Explaining spatial variation in housing construction activity in Turkey - Alkay, Elif; Watkins, Craig; Keskin, Berna (International Journal of Strategic Property Management, 2018)
In Turkey, there has been a strong policy narrative that has emphasized the importance of construction activity as a driver of economic growth. This has given shape to a central state-led policy regime that has sought to ensure that planners and other urban policy makers develop plans and strategies that support construction activity. Against this backdrop, and a recent history of uneven spatial development, this paper seeks to understand what this policy imperative might mean for housing construction activity in different provinces. It seeks to reflect on both the relationship between the state and the market, and the interaction between state policies, economic drivers and levels of construction activity. The evidence presented in the paper suggests that uneven spatial development might be explained in different ways in different provinces. Although, in many cases, patterns of construction activity are consistent with economic fundamentals, there are important exceptions in some regions where arguably activity levels are at odds with prior expectations.